2018
DOI: 10.1017/thg.2018.46
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Trait Analysis of GWAS and Biological Insights Into Cognition: A Response to Hill (2018)

Abstract: Hill (Twin Research and Human Genetics, Vol. 21, 2018, 84-88) presented a critique of our recently published paper in Cell Reports entitled 'Large-Scale Cognitive GWAS Meta-Analysis Reveals Tissue-Specific Neural Expression and Potential Nootropic Drug Targets' (Lam et al., Cell Reports, Vol. 21, 2017, 2597-2613). Specifically, Hill offered several interrelated comments suggesting potential problems with our use of a new analytic method called Multi-Trait Analysis of GWAS (MTAG) (Turley et al., Nature Genetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…Lam et al (2018) assert that their use of multi-trait analysis of genome-wide association study (GWAS) (MTAG; Turley et al, 2018) resulted in the generation of associations that were specific to the trait of cognitive ability. They offer four pieces of supporting evidence based on the genetic correlations derived using linkage disequilibrium score (LDSC) regression (Bulik-Sullivan et al, 2015) found in Table S14 of Lam et al (2018).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Lam et al (2018) assert that their use of multi-trait analysis of genome-wide association study (GWAS) (MTAG; Turley et al, 2018) resulted in the generation of associations that were specific to the trait of cognitive ability. They offer four pieces of supporting evidence based on the genetic correlations derived using linkage disequilibrium score (LDSC) regression (Bulik-Sullivan et al, 2015) found in Table S14 of Lam et al (2018).…”
mentioning
confidence: 99%
“…First, Lam et al (2018) state that ‘our Table S14 demonstrates the set of genetic correlations for the MTAG data differ from those of educational attainment (from the Okbay et al (2016) data set) in many cases by an absolute value (for r g ) of 0.10 or greater’. This characterization of the genetic correlations in Table S14 of Lam et al (2017) differing between the MTAG phenotype and education is misleading.…”
mentioning
confidence: 99%
See 3 more Smart Citations